Aluminoxane-epoxi-siloxane hybrids waveguides - Caiut, Jose Mauricio A. [UNESP]; Rocha, Lucas A. [UNESP]; Sigoli, Fernando A. [UNESP]; Messaddeq, Younes [UNESP]; Dexpert-Ghys, Jeannette; Ribeiro, Sidney José Lima [UNESP] (Elsevier B.V., 2008)
Boehmite-GPTS (GKS-glycidoxypropyltrimethoxysilane) hybrids (BGS) have been prepared by the sol-gel methodology. Spectroscopic properties and structural features have been evaluated from the initial sols to xerogels as a function of composition. Eu3+-containing BGS samples were also prepared, and the Eu3+D0 state emission quantum efficiency was observed to depend on the boehmite-siloxane interactions. Boehmite-siloxane heterocondensation was inferred from vibrational spectroscopy and C-13, Si-29, and Al-27 nuclear magnetic resonance results, Unreacted epoxi groups could be identified in the final material being an important characteristic for the future applications. Good optical quality and mechanical properties lead to the preparation of thin films deposited on glass substrates by dip and spin-coating. Refractive index could be tuned by the relative boehmite and GPTS content. Waveguide properties have also been studied by m-lines spectroscopy and guided modes together with attenuation measurements suggest potential application of the prepared films in integrated optics. (c) 2008 Elsevier B.V. All rights reserved.
Keywords: Optical spectroscopy; Nanocrystals; Nanoparticles; Luminescence; Time resolved measurements; FTIR measurements; Organic-inorganic hybrids; Sol-gels (xerogels)